2013
DOI: 10.1103/physrevlett.111.157205
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Topological Insulator with Tunable Fermi Level: Strainedα-Sn on InSb(001)

Abstract: We report on the epitaxial fabrication and electronic properties of a topological phase in strained α-Sn on InSb. The topological surface state forms in the presence of an unusual band order not based on direct spin-orbit coupling, as shown in density functional and GW slab-layer calculations. Angle-resolved photoemission including spin detection probes experimentally how the topological spin-polarized state emerges from the second bulk valence band. Moreover, we demonstrate the precise control of the Fermi le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
132
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 32 publications
16
132
0
Order By: Relevance
“…The lattices of -Sn and InSb are nearly matched, but a slight mismatch results in an in-plane compressive strain of 0.14% for the -Sn overlayer [19,31]. The crystal structure of (111)-oriented -Sn films is shown in Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The lattices of -Sn and InSb are nearly matched, but a slight mismatch results in an in-plane compressive strain of 0.14% for the -Sn overlayer [19,31]. The crystal structure of (111)-oriented -Sn films is shown in Fig.…”
mentioning
confidence: 99%
“…Liang Fu et al theoretically proposed that such an insulator phase was a strong 3D topological insulator [18]. Two recent experimental studies demonstrated the existence of topological surface states in the valence band regions of -Sn films grown on InSb(001), but no experimental evidence of the strain-induced gap [19,20].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Various approaches have been taken to modulate the electronic properties of stanene. [24][25][26][27][28] Tang et al 27 demonstrated that functionalization on stanene can open up the gap. Furthermore, the substrate plays an important role to tune the electronic properties of stanene due to the strong interaction.…”
Section: Introductionmentioning
confidence: 99%